The perception of boarding schools among students of Sekolah Menengah Seksyen 18, Shah Alam / Wani Nurfahani Mohd Sapuan - Mohd Sapuan, Wani Nurfahani (Faculty of Education, 2011)
The major focus of this research is students’ perceptions of boarding schools since we are often concern of the views of others when students are the ones who stay and learn in school. The research is conducted at Sekolah Menengah Seksyen 18, Shah Alam. The school is selected since it consists of boarders and non-boarders. This meets the requirement of this research to obtain the students’ perceptions of boarding schools from both boarders and non-boarders of the same school. 50 students with 25 boarders and 25 non-boarders from two classes of Form 3 are taken as the sample of this research. In a form of questionnaires, survey research is conducted to collect data for this research. The questions feature items such as students’ status, grade and perceptions. The students’ perception of boarding schools is divided into three major parts which are; preferences, self-betterment and better education. The data is analysed using Statistical Package for the Social Sciences (SPSS). Descriptive Analysis was run to find the result of the first and second research questions whereas the third research question was analyzed using Pearson Correlation Test. The three research questions are; 1) What are the students’ perception towards boarding school? 2) Does the academic achievement of boarding students differ from the non-boarding students? 3) Does the students’ perception towards boarding schools affect their academic achievement? The results of this research are positive. Students prefer to be in boarding schools compared to day schools. Furthermore, students agree that boarding schools promote self-betterment and offer better education to students. However, the result shows that non-boarders achieve better grades than boarders although students (boarders and non-boarders) prefer to be in boarding schools. Thus, this explains the negative correlation between the academic achievement of students and students’ perceptions whether to be in boarding or day school.